TINJAUAN PROSES PENGEMBANGAN DESTINASI WISATA GAYO CAMPING GROUND DI TAKENGON ACEH - Bilqistina Bilqistina; Apriliani Lase (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
The objectives of this research are to: 1) determine the plan for maximising Gayo Takengon Campgrounds' tourist potential; and 2) provide management of the campgrounds' attractions with guidance. This study discusses the potential and how to create it using a sort of qualitative research and descriptive data analysis. The study's findings indicate that there is potential for development into a natural tourist attraction. These possibilities are: 1) As the Gayo Camping Ground develops as a tourism object, the promotion strategy is currently quite effective. For instance, the tourism office has promoted by providing promotional flyers and videos, which were then uploaded to social media, which is directly managed by the Gayo Camping Ground manager himself. The availability of this material on social media platforms like Instagram, Facebook, and YouTube makes it simpler for travellers to find out more about this tourist destination. 2) Based on the findings of this research, there aren't many improvements that need to be made to the Gayo Campground tourist attraction as all of its amenities already match the requirements for a tour.